Forvaltningens organisering og mediernes placering af det politiske ansvar - Mortensen, Peter Bjerre (Politik, 2011)
Under what conditions and to what extent is a minister attributed responsibility in the media when things go wrong within an agency or an enterprise that belongs to the jurisdiction of the minister’s department? This question about delegation and responsibility is important, but has never been subject to systematic empirical analysis. Based on a coding of more than 5,000 Danish national newspaper articles about the Danish national railway company (DSB) from 1995 to 2007, this paper examines the role of the minister of transportation more closely.